Pengembangan UMKM Melalui Sosialisasi dan Penyuluhan Secara Digital untuk Menunjang Keberlangsungan Usaha di Masa Pandemi Covid-19 - Andi Erna Mulyana; Rahmat Hidayat; Nur Rahmah Andayani; Sri Zuliarni; Aditya Wirangga Pratama; Maryani Septiana; Hajan Hidayat; Yulinda Yulinda; Diah Amaliah; Muhammad Ikhlash; Sugeng Riadi; Desi Ratna Sari; Slamet Soebagiyo (Pusat P2M Politeknik Negeri Batam, 2021)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in the economy of Indonesian society. The existence of MSMEs is very useful in terms of distributing people's income. From this point, it is necessary to carry out training to support the sustainability of MSMEs and help them overcome various problems, from the management aspect to the capital aspect. Especially during the pandemic Covid-19, where many MSMEs are threatened with their survival. For this reason, the purpose of the community service activities that will be carried out with the method of socialization and counseling through the digital system is to provide information and additional knowledge needed by MSMEs. The information and knowledge provided will be packaged in the form of socialization and counseling videos. The results of the activities were the socialization and counseling materials in digital form that could be accessed by MSMEs by utilizing the current information technology.